#AMFAD : all my friends are dead [videorecording (DVD)] - Sims, Josh; Thomas, Paul Michael; Pettyjohn, Jade, 2000-; Siwa, JoJo, 2003-; Ens, Jennifer (Cineverse, 2024)
A group of college friends rent an Airbnb for the biggest music festival of the year. A weekend of partying quickly takes a turn, as the group is murdered one by one, in correspondence with the seven deadly sins.